Body Size and Morph as Drivers of Copulation Duration in a Male Dimorphic Damselfly. (14th March 2013) - Wong‐Muñoz, Jesus; Anderson, Chris N.; Munguía‐Steyer, Roberto; Córdoba‐Aguilar, Alex; Koenig, W.
Abstract Copulation duration is often highly variable within and among species. Here, we explore the roles of body size, male morph, morph frequency, and alternative reproductive tactics to explain copulation duration in the damselfly Paraphlebia zoe. P. zoe has two male morphs (pigmented or hyaline wings) which differ in reproductive tactics (territorial or non‐territorial behaviors). We also analyze the effects of season as the frequencies of both morphs tend to vary along the reproductive season. In the first non‐experimental year, we found that the relationship between body size and copulation duration depended on the time of year. Early in the season, body size positively correlated with copulation duration, while late in the year, body size negatively correlated with copulation duration. In the second experimental year (when we reversed the frequency of male morphs in the middle of the season: making pigmented males less frequent than hyaline males), size influenced copulation duration as well as morph – body size positively correlated with copulation duration, and hyaline males mated for longer than pigmented males. Contrary to our prediction, changes to the relative abundances of morphs did not influence copulation duration. Hyaline males may be under selection for longer copulation durations to compensate for their reduced access to females, as long copulations potentially lead to more rival sperm to be removed from the female sperm storage organs and/or increased mate guarding. We do not discard, however, other explanations that drive variation in copulation duration such as cryptic female choice and/or predation.